Porosity in the Final Denture-A heartbreak ! - Maskey, B; Khanal, G (Journal of Nepalese Prosthodontic Society, 2023)
Porosities in the aftermath of a polymerization defect occurring in a complete denture are incidental in some cases with time constraints, though unintentional. Such defects harbor microbial colonization, compromise mechanical and aesthetic properties, and at times are even unserviceable to the patient. Remaking the denture right before insertion is disheartening in these instances, both for the patient and the attending clinician. This clinical report describes a rebasing technique that was undertaken to replace a fragile denture base.